Anticholinergic medications in patients admitted with cognitive impairment or falls (AMiCI). The impact of hospital admission on anticholinergic cognitive medication burden. Results of a multicentre observational study. (4th May 2018) - Weichert, I.; Romero‐Ortuno, R.; Tolonen, J.; Soe, T.; Lebus, C.; Choudhury, S.; Nadarajah, C. V.; Nanayakkara, P.; Orrù, M.; Di Somma, S.; ,
Summary: What is known and objective: Drugs with anticholinergic properties increase the risk of falls, delirium, chronic cognitive impairment, and mortality and counteract procholinergic medications used in the treatment of dementia. Medication review and optimisation to reduce anticholinergic burden in patients at risk is recommended by specialist bodies. Little is known how effective this review is in patients who present acutely and how often drugs with anticholinergic properties are used temporarily during an admission. The aim of the study was to describe the changes in the anticholinergic cognitive burden (ACB) in patients admitted to hospital with a diagnosis of delirium, chronic cognitive impairment or falls and to look at the temporary use of anticholinergic medications during hospital stay. Methods: This is a multi‐centre observational study that was conducted in seven different hospitals in the UK, Finland, The Netherlands and Italy. Results and discussion: 21.1% of patients had their ACB score reduced by a mean of 1.7%, 19.7% had their ACB increased by a mean of 1.6%, 22.8% of DAP naïve patients were discharged on anticholinergic medications. There was no change in the ACB scores in 59.2% of patients. 54.1% of patients on procholinergics were taking anticholinergics. Out of the 98 medications on the ACB scale, only 56 were seen. Medications with a low individual burden were accounting for 64.9% of the total burden. Anticholinergic drugs were used temporarily during the admission in 21.9% of all patients. A higher number of DAPs used temporarily during admission was associated with a higher risk of ACB score increase on discharge (OR = 1.82, 95% CI for OR: 1.36‐2.45, P < .001). What is new and conclusion: There was no reduction in anticholinergic cognitive burden during the acute admissions. This was the same for all diagnostic subgroups. The anticholinergic load was predominantly caused by medications with a low individual burden. More than 1 in 5 patients not taking anticholinergics on admission were discharged on them and similar numbers saw temporary use of these medications during their admission. More than half of patients on cholinesterase‐inhibitors were taking anticholinergics at the same time on admission, potentially directly counteracting their effects. Abstract : Drugs with anticholinergic properties increase the risk of falls, delirium, chronic cognitive impairment and mortality and counteract procholinergic medications used in the treatment of dementia. This is a multicentre observational study that was conducted in 7 different hospitals in the UK, Finland, the Netherlands and Italy to investigate the change in anticholinergic cognitive burden in unscheduled emergency medical admissions. Despite a quarter of a century of evidence and guidance by specialist bodies, no change in anticholinergic burden took place in patients at risk of anticholinergic effects.